Global and regional distribution of HIV-1 genetic subtypes and recombinants in 2004. - Hemelaar, J; Gouws, E; Ghys, P; Osmanov, S (2006)
OBJECTIVE: To estimate the global and regional distribution of HIV-1 subtypes and recombinants in 2004. DESIGN: A study was conducted in which molecular epidemiological data on HIV-1 subtype distribution in individual countries were combined with country-specific estimates of the number of people living with HIV. METHODS: HIV-1 subtype data were collected for 23 874 HIV-1 samples from 70 countries, which together accounted for 89% of all people living with HIV worldwide in 2004. The proportions of HIV-1 infections due to various subtypes detected in each country were combined with the number of HIV infected people in the respective countries to generate regional and global HIV-1 subtype distribution estimates. RESULTS: Subtype C accounted for 50% of all infections worldwide in 2004. Subtypes A, B, D and G accounted for 12%, 10%, 3% and 6%, respectively. The subtypes F, H, J and K together accounted for 0.94% of infections. The circulating recombinant forms CRF01_AE and CRF02_AG each were responsible for 5% of cases, and CRF03_AB for 0.1%. Other recombinants accounted for the remaining 8% of infections. All recombinant forms taken together were responsible for 18% of infections worldwide. CONCLUSION: Combining data on HIV-1 subtype distribution in individual countries with country-specific estimates of the number of people living with HIV provided a good method to generate estimates of the global and regional HIV-1 genetic diversity in 2004. The results could serve as an important resource for HIV scientists, public health officials and HIV vaccine developers.